Impact of ICT on the structural and contextual organizational elements: Case of the Varaždin County - Brodar, Kristina (Array, 2009)
Summary: The influence of certain factors on the organizational components has been in researchers' focus for years, together with their impact on the overall organizational efficiency. Traditional view commonly divided the factors on internal and external ones, which became improper in modern conditions. With contemporary division on structural and contextual factors, as a specific determinant we have to extract information and communication technology (ICT) which impacts elements of structural and contextual dimension in every organization. Therefore it is becoming generic factor which cannot be classified into one of these groups. In this research, we observed impact of ICT on organizational elements of public administrations offices on the case of the Varaždin County. Results show that this impact is present in various forms in all observed factors and thus makes ICT a generic organizational factor.